Spectrum of renal disease in diabetes. Issue 9 (September 2014) - Teng, Jessie; Dwyer, Karen M; Hill, Prue; See, Emily; Ekinci, Elif I; Jerums, George; MacIsaac, Richard J
Abstract The spectrum of renal disease in patients with diabetes encompasses both diabetic kidney disease (including albuminuric and non‐albuminuric phenotypes) and non‐diabetic kidney disease. Diabetic kidney disease can manifest as varying degrees of renal insufficiency and albuminuria, with heterogeneity in histology reported on renal biopsy. For patients with diabetes and proteinuria, the finding of non‐diabetic kidney disease alone or superimposed on the changes of diabetic nephropathy is increasingly reported. It is important to identify non‐diabetic kidney disease as some forms are treatable, sometimes leading to remission. Clinical indications for a heightened suspicion of non‐diabetic kidney disease and hence consideration for renal biopsy in patients with diabetes and nephropathy include absence of diabetic retinopathy, short duration of diabetes, atypical chronology, presence of haematuria or other systemic disease, and the nephrotic syndrome.